FEEDBACK STRATEGIES TEACHING WRITING ONLINE DURING COVID-19 - Abdurahman Hi Usman; Abdulhalim Daud; Suratman Dahlan; Adi F Mahmud (Cakrawala Bahasa, 2020)
Teaching writing as a process at the university level leads lecturers to give feedback on students’ writing drafts. This research aims to investigate the feedback strategies used by the lecturer in giving feedback to students. This is a qualitative case study research designed for several reasons. This study was conducted in a natural setting in which the researcher focus on feedback strategies used by lecturersto respond to students’ writing drafts. A purposive sample was used in choosing the subject of this research (Alwasilah, 2012). The instrument of this study were researchers. Researchersactas non-participant of an observer (Djam'an Satory and Aan Komariah, 2010). This study was conducted at Universitas Khairun Ternate. The subjects of this research were fourth-semester students who study essay writing online. Data of this study were obtained from students’ documents. Content analysis was focused in this study. The findings in this research were consistent with the ones presented by several scholars in teaching writing.There were several feedback strategies used to respond to students’ writing, namely indirect feedback, direct feedback, and commentary feedback to respond to students’ writing.